Harmonisasi Regulasi Pengadaan Barang/Jasa di Desa: Antara Akuntabilitas Fiskal dan Otonomi Desa: Regulatory Harmonization of Public Procurement in Villages: Between Fiscal Accountability and Village Autonomy - Mian Felicity; Dian Tanila Chrismawati (Badan Pembinaan dan Pengembangan Hukum Pemeriksaan Keuangan Negara Badan Pemeriksa Keuangan RI, 2026)
The incorporation of village governments into the national Government Procurement of Goods/Services (PBJP) regime under Presidential Regulation No. 46 of 2025 generates a normative tension between standardized procurement requirements and village autonomy. This study analyzes the resulting regulatory disharmony, particularly the interaction between the national PBJP framework and the village-specific procurement regime under National Public Procurement Agency Regulation No. 12 of 2019. Using normative legal research with statutory and conceptual approaches, supported by systematic and teleological interpretation, the study finds a structural misalignment between uniform, digitalized procurement standards and the diverse administrative capacities of village governments. This misalignment reflects a broader implementation burden–capacity gap, increasing the likelihood of procedural non-compliance and inefficiencies in public spending. The findings indicate that the core problem lies in a normative misfit between administrative uniformity and asymmetrical decentralization, where village governance prioritizes substantive accountability rooted in community-based practices. This article offers a novel contribution by positioning village procurement as a sui generis legal regime and proposing a harmonization model based on risk-based procurement, differentiated capacity standards, and smart decentralization to balance fiscal accountability with village autonomy.